From glucose sensing to exocytosis: takes from maturity onset diabetes of the young - Samadli, Sama; Zhou, Qiaoli; Zheng, Bixia; Gu, Wei; Zhang, Aihua (Frontiers in Endocrinology, 2023)
Monogenic diabetes gave us simplified models of complex molecular processes occurring within β-cells, which allowed to explore the roles of numerous proteins from single protein perspective. Constellation of characteristic phenotypic features and wide application of genetic sequencing techniques to clinical practice, made the major form of monogenic diabetes – the Maturity Onset Diabetes of the Young to be distinguishable from type 1, type 2 as well as neonatal diabetes mellitus and understanding underlying molecular events for each type of MODY contributed to the advancements of antidiabetic therapy and stem cell research tremendously. The functional analysis of MODY causing proteins in diabetes development, not only provided better care for patients suffering from diabetes, but also enriched our comprehension regarding the universal cellular processes including transcriptional and translational regulation, behavior of ion channels and transporters, cargo trafficking, exocytosis. In this review, we will overview structure and function of MODY causing proteins, alterations in a particular protein arising from the deleterious mutations to the corresponding gene and their consequences, and translation of this knowledge into new treatment strategies.